2013
DOI: 10.5007/2175-7925.2013v26n1p203
|View full text |Cite
|
Sign up to set email alerts
|

Predation on artificial nests by marmosets of the genus Callithrix (Primates, Platyrrhini) in a Cerrado fragment in Southeastern Brazil

Abstract: ResumoPredação de ninhos artificiais por saguis do gênero Callithrix (Primates, Platyrrhini) em um fragmento de Cerrado no Sudeste do Brasil. Embora as causas de declínio em populações de aves em fragmentos florestais não sejam bem conhecidas, a predação de ninhos parece desempenhar um papel importante nesses eventos. Um modo de estimar a importância relativa da predação na reprodução de aves nativas é a utilização de ninhos artificiais. São apresentadas aqui altas taxas de predação de ninhos artificiais por d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Almeida et al (2013) found high levels of predation on artificial nests by these marmosets and their hybrid derivates, suggesting that it may also occur in natural nests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almeida et al (2013) found high levels of predation on artificial nests by these marmosets and their hybrid derivates, suggesting that it may also occur in natural nests.…”
Section: Discussionmentioning
confidence: 99%
“…Both species are invading and possibly replacing other species in many regions of eastern Brazil, such as in the states of Minas Gerais, Espírito Santo, São Paulo, and Rio de Janeiro (Rylands et al, 2009), reaching the southern by a the state of Santa Catarina (Santos et al, 2005). In addition, inside the new habitats where they previously not occurred, these species may act as invaders, with potential damage to the preexisting biota, such as by predation of bird´s eggs (Alexandrino et al, 2012;Almeida et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to competition between exotic and native species, the introduction of C. penicillata and C. jacchus can result in predation against native fauna (Vale & Prezoto, 2015). They may endanger local populations of birds by using eggs and offspring as a food source (Passos et al, 2006;Galleti et al, 2009;Gomes & Lima-Gomes, 2011;Alexandrino et al, 2012;Almeida et al, 2013), as well as other taxa, such as reptiles First record of Callithrix penicillata in Northern Paraná. and small amphibians (Rangel et al, 2011;Vale & Prezoto, 2015).…”
Section: 131mentioning
confidence: 99%